BCG Vaccination Induces M. avium and M. abscessus Cross-Protective Immunity - Abate, Getahun; Hamzabegovic, Fahreta; Eickhoff, Christopher S.; Hoft, Daniel F. (Frontiers in Immunology, 2019)
Pulmonary nontuberculous mycobacterial (NTM) infections particularly caused by Mycobacterium avium complex (MAC) and M. abscessus (MAB) are becoming major health problems in the U.S. New therapies or vaccines which will help prevent the disease, shorten treatment duration and/or increase treatment success rate are urgently needed. This study was conducted with the objective of testing the hypothesis that Bacillus Calmette Guerin (BCG), a vaccine used for prevention of serious forms of tuberculosis in children and adolescents in tuberculosis (TB) hyperendemic countries, induces cross-protective T cell immunity against M. avium (MAV) and MAB. TB and NTM cross-protective T cells were quantified using flow cytometric assays. The ability of BCG expanded T cells to inhibit the intracellular growth of MAV and MAB was assessed in co-cultures with infected autologous macrophages. In both BCG-vaccinated and M. tuberculosis (Mtb)-infected mice, NTM cross-protective immunity was measured using IFN- ELISPOT assays. Our results demonstrate the following key findings: i) peripheral blood mononuclear cells from TB skin test-positive individuals contain MAV and MAB cross-reactive T cells, ii) both BCG vaccination and Mtb infection of mice induce MAV and MAB cross-reactive T cells, iii) BCG-expanded T cells inhibit intracellular MAV and MAB, iv) CD4, CD8, and  T cells play important roles in inhibition of intracellular MAV and MAB and v) BCG vaccination of healthy volunteers induces TB and NTM cross-protective T cells. In conclusion, BCG-vaccination induces NTM cross-protective immunity, and has the potential for use as a vaccine or immunotherapy to prevent and/or treat pulmonary NTM disease.